Navigating the Dynamics of Corporate Financial Management for Sustainable Growth - Simanjuntak, Renova (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
This literature review aims to investigate the integration of sustainability principles into financial management practices and its implications for organizational strategies and outcomes. The research methodology involves a systematic review of existing literature on corporate financial management and sustainable growth. Utilizing qualitative analysis, the study synthesizes findings from a diverse range of scholarly sources to elucidate the complex dynamics shaping organizational strategies and outcomes. The findings reveal a robust correlation between effective financial management practices and sustainable growth outcomes, highlighting the strategic significance of integrating sustainability considerations into financial decision-making processes. Key themes identified include the role of financial management in driving sustainable growth initiatives, fostering resilience, and creating long-term value for stakeholders. Moreover, the study underscores the importance of leadership commitment, stakeholder engagement, and technological innovation in advancing sustainable financial management practices. Despite the progress made, challenges such as regulatory constraints, market pressures, and cultural inertia pose significant barriers to mainstreaming sustainability within organizations. The findings have implications for theory, practice, and future research, emphasizing the need for organizations to embrace an integrated approach to financial management that prioritizes sustainability considerations.